2023
DOI: 10.1177/02656590231154827
|View full text |Cite
|
Sign up to set email alerts
|

Language development of Chinese-speaking hearing-impaired children: The roles of home literacy resources and shared book reading

Abstract: The present study aimed to explore the specific components of home literacy resources (HLR) and parental behaviours during shared book reading (SBR) that may contribute to the language development of Chinese-speaking hearing-impaired children. A total of 90 Chinese-speaking hearing-impaired children aged 3 to 6 years, along with their parents, participated in this study. Following the design of previous studies, we required the parents to complete a questionnaire regarding HLR and parental SBR behaviours, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…More research is required to find the best strategy for assisting vocabulary development in these populations. These studies have shown promising results, highlighting the significance of including sensory modalities compatible with this population's communication preferences and skills (Chan, 2023;Cadime et al, 2018;Melany et al, 2023). Sensory modalities significantly influence the development of vocabulary.…”
Section: B Previous Studies On Vocabulary Instruction For Speaking An...mentioning
confidence: 99%
“…More research is required to find the best strategy for assisting vocabulary development in these populations. These studies have shown promising results, highlighting the significance of including sensory modalities compatible with this population's communication preferences and skills (Chan, 2023;Cadime et al, 2018;Melany et al, 2023). Sensory modalities significantly influence the development of vocabulary.…”
Section: B Previous Studies On Vocabulary Instruction For Speaking An...mentioning
confidence: 99%